Prognostic power of conventional echocardiography in individuals without history of cardiovascular diseases: A systematic review and meta-analysis - Fernandes, Luciana Pereira (2021)
Echocardiographic abnormalities are associated with a higher incidence of adverse cardiovascular outcomes. This systematic review and meta-analysis aimed to evaluate whether echocardiographic abnormalities are predictors of cardiovascular events in individuals without previous cardiovascular diseases. The PubMed, Scopus, and SciELO databases were searched for longitudinal studies investigating the association between echocardiographic abnormalities and cardiovascular events among individuals without known cardiovascular diseases. Two independent reviewers analyzed data on the number of participants, age and sex, echocardiographic alterations, follow-up time, and cardiovascular outcomes. The meta-analysis estimated the risk ratio (RR) and 95% confidence interval (CI). Heterogeneity was assessed using I2 test. Twenty-two longitudinal studies met the eligibility criteria, comprising a total of 55,603 patients. Left ventricular hypertrophy (LVH) was associated with non-fatal cardiovascular events (RR 2.16; 95% CI 1.22-3.84), death from cardiovascular disease (RR 2.58; 95% CI 1.83- 3.64), and all-cause mortality (RR 2.02; 95% CI 1.34-3.04). Left ventricular diastolic dysfunction (LVDD) and left atrial dilation (LA) were associated with fatal and non-fatal cardiovascular events (RR 2.01; 95% CI 1.32-3.07) and (RR 1.78; 95% CI 1.16-2.73), respectively. Aortic root dilation was associated with non-fatal cardiovascular events (RR 1.25; 95% CI 1.09-1.43). In conclusion, LVH, LVDD, dilations of the LA, and of the aortic root were associated with an increased risk of adverse events in individuals without previous cardiovascular diseases. This study suggests that simple data obtained on conventional echocardiography can be an important predictor of cardiovascular outcomes in a low-risk population.